2020
DOI: 10.4236/ojmm.2020.104015
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Antibiotic Resistant Index of Gram-Negative Bacteria from Bird Droppings in Two Commercial Poultries in Enugu, Nigeria

Abstract: Antimicrobial resistance refers to the ability of microorganisms to grow in the presence of an antimicrobial agent at a concentration that will normally kill or inhibit their growth. Antimicrobial resistance has become a major global threat making treatment of infections tougher especially with high cost of treatment in humans and animals. This study was done to determine the Multiple Antibiotic Resistant Index (MARI) of Gram-negative bacteria from bird droppings in two commercial poultries in Enugu. Forty (40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 14 publications
2
21
1
Order By: Relevance
“…Organisms that have MARI greater than 0.2 confirm the presence of multidrug-resistant genes originating from the environment where there is an abuse of these drugs. Also, that the plasmids contain one or more resistance genes each encoding a single antibiotic resistance phenotype (Afunwa et al, 2020). The widespread of multidrug-resistant Pseudomonas aeruginosa in the community reveals that there is a proliferation of patent vendors illegally and unprofessionally prescribing and dispensing antibiotics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organisms that have MARI greater than 0.2 confirm the presence of multidrug-resistant genes originating from the environment where there is an abuse of these drugs. Also, that the plasmids contain one or more resistance genes each encoding a single antibiotic resistance phenotype (Afunwa et al, 2020). The widespread of multidrug-resistant Pseudomonas aeruginosa in the community reveals that there is a proliferation of patent vendors illegally and unprofessionally prescribing and dispensing antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…The widespread of multidrug-resistant Pseudomonas aeruginosa in the community reveals that there is a proliferation of patent vendors illegally and unprofessionally prescribing and dispensing antibiotics. This resistance to frontline antibiotics could also be connected to indiscriminate use of antibiotics in poultry breeding and the subsequent consumption of such poultry may have transferred the resistance to humans (Afunwa et al, 2020). This is worrisome because the multidrugresistant isolates were from residential areas and not from the hospitals.…”
Section: Resultsmentioning
confidence: 99%
“…The MAR index for each bacterial isolate and poultry farm sample was calculated based on the method described by Krumperman ( 5 ). MAR index values of <0.2 indicate a low risk of ARB contamination, while values of ≥0.2 indicate a high risk of ARB contamination ( 5 , 6 ).…”
Section: Observationmentioning
confidence: 99%
“…Figure 1 shows the distribution of MAR indices of the isolates. Bacterial species with a MAR index of ≥0.2 indicate a likelihood of origination from a high-contamination area, where antibiotics had been used extensively ( 6 ). Furthermore, the Kruskal-Wallis test showed that the bacteria exhibited significantly high percentage of AR and MAR index values ( P < 0.0001).…”
Section: Observationmentioning
confidence: 99%
“…The high incidence of antimicrobial resistance is of concern to international agencies such as the World Health Organization (WHO), the Food and Agriculture Organization (FAO), and the World Organization for Animal Health (OIE) [6]. Incidence of antibiotic resistance can contaminate products from livestock and potentially be a source of microbial contamination to humans, which is very influential in increasing the economic value of overcoming microbial resistance.…”
Section: Introductionmentioning
confidence: 99%